Simulation of deformation and fracture processes in nanocomposites (Fracture and Structural Integrity, 2019)
The paper studies the processes of deformation and fracture in nanocomposites. The study was curry out by the method of mathematical modeling. The behavior of the nanosystem was described by the molecular dynamics apparatus. A modified immersed atom method was used as a potential. Demonstrated theoretical approaches to the study of the mechanical properties of nanocosposites and the processes of their destruction. Formulas for calculating the stress, strain tensors and displacement veare given. To maintain a constant temperature in the nanosystem, a Nose – Hoover thermostat was used. The destruction of nanocomposites was considered in the process of tension and shear deformation. Pure aluminum, a composite with an aluminum matrix and a filler in the form of spherical iron particles, and a composite with an aluminum matrix and a filler in the form of a cylindrical iron fiber were used as samples. After the filler was introduced into the nanocomposite, the sample was relaxed to ensure its more stable state. The simulation allowed us to establish the basic laws of changes in the atomic structure of the matrix and nanocomposite fillers during deformation and fracture. It is shown that the processes of deformation and destruction of nanocomposites substantially depend both on the structure and types of loading of the material. The results of the research can be used to study the processes of deformation of nanocomposite materials with promising functional properties.
Keywords: Nanostructures; Nanocomposites; Molecular dynamics; Deformation; Rupture